Respuesta :
Answer: -2a^3 + 9a^2 + 45a + 18b^2 + 6ab^2
Step-by-step explanation:
(a + 3) * (-2a^2 + 15a + 6b^2)
We open the brackets with (a + 3)
a ( -2a^2 + 15a + 6b^2) + 3(-2a^2 + 15a + 6b^2)
Opening the brackets
= a * -2a^2 = -2a^3
a * 15a = 15a^2
a * 6b^2 = 6ab^2
3 * -2a^2 = -6a^2
3 * 15a = 45a
3 * 6b^2 = 18b^2
Let's arrange those values weve gotten together ,don't forget the signs each carry
= -2a^3 + 15a^2 + 6ab^2 - 6a^2 + 45a + 18b^2
Collect the like terms
= -2a^3 + 15a^2 - 6a^2 + 6ab^2 + 45a + 18b^2
= -2a^3 + 9a^2 + 6ab^2 + 45a + 18b^2
Answer:
c: -2a^3+9a^2+45a+6ab^2+18b^2
Step-by-step explanation:
i just did on edgen 2020